Automating Everyday Activities: A Study on the Usage of Text-Based AutoCorrect among Age Groups. (September 2022) - Frazier, Shree N.; McComb, Sara A.; Pitts, Brandon J.
Automation has infiltrated nearly all areas of our lives. Many technologies have not been designed considering older adult populations. Smartphone usage is pervasive among older individuals, but whether age-related differences exist in the use of automated features of mobile devices continues to be researched. This study examined how younger, middle-aged, and older adults use AutoCorrect (AC) to send mobile messages. A total of 138 participants were asked about their perceptions of AC and to write messages in response to four scenarios that varied in complexity. Overall, younger adults had a more favorable perception of AC compared to middle-aged and older adults. Also, when complexity was both high and low, older adults were more likely to proofread their messages, manually correct AC, find AC distracting, and perceive AC to be helpful. Our findings suggest that older adults do engage with automation differently than their younger counterparts, which should be considered by automation designers.